Transport Organisation in a Great City: The Case of London - Collins, Michael F.; Pharoah, Timothy M.; London School of Economics and Political Science (London: Allen and Unwin [for] the L.S.E., 1974)
This study concentrates more on passenger transport, and the nature and operation of a complex structure of institutions which are responsible for planning and operating the networks of transport facilities and services in London.
Includes bibliographical references and index.
ne 26/02/2018
Loan
Keywords: Transportation and State; Local transit